Konstitusionalitas Pembatasan Hak Mantan Narapidana untuk Menjadi Notaris - Salsabila, Aizahra Dafa; Muktiono, Muktiono; Sulistio, Faizin (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This article aimsto discussthe juridical analysis of the provisions which state that former convicts cannot become notaries. The type of method used is normative juridical with a statutory approach, conceptual approach and historical approach. Legal material sources consist of primary and secondary legal materials, analysis techniques using grammatical and theological interpretation. The provisions of Law Number 2 of 2014 in Article 3 letter h which states that the condition for becoming a notary isto never be subject to imprisonment for a minimum of five years or more is unclear and unfair. Limiting the length of sanctions regardless of the type of criminal act is not appropriate, there should be certain types of criminal acts related to the notary profession or the code of ethics that is the reference. In several regulations there are criminal offenses that carry a sentence of less than five years, however the criminal offenses committed are closely related to the professionalism that a notary must possess. This provision also does not provide a sense of justice because someone who has served his sentence means that he has received sanctions for the actions he has committed and has the right to get a decent job as regulated in Article 27 and Article 28 of the 1945 Constitution of the Republic of Indonesia.